Genome-wide identification of the opsin protein in Leptosphaeria maculans and comparison with other fungi (pathogens of Brassica napus) - Mohri, Marzieh; Moghadam, Ali; Burketova, Lenka; Ryšánek, Pavel (Frontiers in Microbiology, 2023)
The largest family of transmembrane receptors are G-protein coupled receptors (GPCRs). These receptors respond to perceived signals from their environment and infect their host plants.Family A of the GPCR includes opsin. There is less known about the roles of GPCRs in phytopathogenic fungi. We studied opsin in Leptosphaeria maculans, an important pathogen of oilseed rape (Brassica napus) that causes blackleg disease, and compared with six other fungal pathogens of oilseed rape. Phylogenetic tree analysis of 31 isoforms of opsin protein showed six major groups and six subgroups. All three opsin isoforms of L. maculans are grouped in the same clade in the phylogenetic tree. Physicochemical analysis revealed that all studied opsin proteins are stable and hydrophobic. Subcellular localization revealed that most isoforms were localized in the endoplasmic reticulum membrane except several isoforms in Verticillium species, localized in the mitochondrial membrane. Most isoforms comprise two conserved domains. One conserved motif was observed across all isoforms, consisting BACTERIAL_OPSIN_1 domain, which is hypothesized to have an identical sensory function.Most studied isoforms showed seven transmembrane helices except one isoform of V. longisporum and four isoforms of F. oxysporum. Tertiary structure prediction displayed a conformational change in four isoforms of F. oxysporum presumed differences in the binding to other proteins and sensing signals, thereby resulting in various pathogenicity strategies.Protein-protein interactions and binding site analysis demonstrated varieties number of ligands and pockets across all isoforms, ranging between 0-13 ligands and 4-10 pockets. According to the phylogenetic analysis in this study and considerable physiochemically and structurally differences of opsin proteins among all studied fungi hypothesized that this protein acts in the pathogenicity, growth, sporulation, and mating of these fungi differently.